Percentage of Hard Coral Cover and Coral Recruitment on in Bangsring Beach, Banyuwangi Regency - Samuel, Pratama Diffi; Fakhri, Muhammad; Dewi, Citra Satrya Utama; Ellona, Jessica; Anam, M. Choirul (Research Journal of Life Science, 2023)
One of the tourist attractions at Bangsring Beach is the condition of the coral reef ecosystem and unique marine biota that tourists can enjoy by snorkeling and diving. Based on research (Ekawati et al., 2021) using remote sensing, the area of live coral reefs on Bangsring Beach is as follows; 2005; 3.38, 2008; 2.61, 2011; 3.7, 2017; 3.98, 2020; 6.1 Ha). It can be said that the area of coral reefs increases yearly, although, in 2008-2011, it decreased by 32%. The results of the economic valuation explain that the (Total Economic Value) of the coral reef ecosystem in Bangsring Beach is 38.2 billion Rupiah/year or 2.9 billion Rupiah hectares/year. The use-value that has the largest economic value comes from tourism utilization of 25 billion or 60% of the Total Economic Value. The coral community structure includes Coral Branching, Coral Encrusting, Coral Massive, Coral Submaasive, and Coral Mushroom. Mushroom Coral is found solitary and shaped like a mushroom. The research data shows the average value of Bangsring Fish House cover is 82.5%. Fish house cover here is seen and assessed based on the presence of hard corals, soft corals, and algae. The average percentage of hard corals growing at the Bangsring Fish House was 30%, soft corals 21.5%, and algae 17.5%. Found 21 types of coral such as; Acropora, Favia, Turbinaria, Symphyllia, Goniastrea.